Aging2Cancer: an integrated resource for linking aging to tumor multi-omics data - Dahua Xu; Yutong Shen; Nihui Zhang; Guoqing Deng; Dehua Zheng; Peihu Li; Jiale Cai; Guanghui Tian; Qingchen Wei; Hongyan Jiang; Jiankai Xu; Bo Wang; et al. (BMC Genomics)
Abstract Background Aging and tumorigenesis share intricate regulatory processes, that alter the genome, epigenome, transcriptome and immune landscape of tissues. Discovering the link between aging and cancer in terms of multiomics characteristics remains a challenge for biomedical researchers. Methods We collected high-throughput datasets for 57 human tumors and 20 normal tissues, including 23,125 samples with age information. On the basis of these sufficient omics data, we introduced six useful modules including genomic (somatic mutation and copy number variation), gene expression, DNA methylation, hallmarks (aging and cancer), immune landscape (immune infiltration, immune pathways, immune signatures, and antitumor immune activities) and survival analysis. Correlation and differential analyses were performed for the multiomic signatures associated with aging at the gene level. Results We developed Aging2Cancer ( http://210.37.77.200:8080/Aging2Cancer/index.jsp ), which is a comprehensive database and analysis platform for revealing the associations between aging and cancer. Users can search for and visualize the results of genes of interest to explore the relationships between aging and cancer at the gene level for different omics levels. Conclusions We believe that Aging2Cancer is a valuable resource for identifying novel biomarkers and will serve as a bridge for linking aging to cancer.